Temporal Analysis of Multispectral Satellite Data for the Purpose of Urbanization Monitoring - V. Kević; I. Racetin; A. Krtalić (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Monitoring the urbanization process and early detection of illegal construction should enable meaningful urban planning and the protection of natural and cultural features of the community. There is a major problem of illegal construction in the Republic of Croatia. In 2023 alone, according to a report by the State Inspectorate of the Republic of Croatia, a total of 4,774 inspections were carried out on the territory of the Republic of Croatia, and 1,089 inspection procedures were initiated due to violations of construction regulations. The aim of this paper was to examine and determine the possibilities of applying remote sensing methods in the early detection of areas under construction or other types of devastation. The evaluation of the quality and usability of the results refers to reliability of the detection of areas under construction using the images of the Sentinel-2 and PlanetScope satellite systems. In order to detect those areas, ten spectral indices were for two reference dates one in 2017 and 2021 (nine indices for Sentinel-2 and one for Planetscope). The results of this research include analysis of spectral indices for detection and identification of land parcels that exhibit land cover changes from natural to human construction. The city of Solin and Podstrana municipality (near Split, Croatia), with its wider surroundings, were selected for the research area. The best results were achieved with the difference of NDVI spectral indices calculated using the spectral channels of the Sentinel-2 and PlanetScope satellite systems. Achieved results, showed also that the spatial resolution of the used spectral bands (3 m PlanetScope and 10 m Sentinel-2) did not have a major impact on the accuracy of detection for this specific application.